2021
DOI: 10.1590/1678-9865202134e200295
|View full text |Cite
|
Sign up to set email alerts
|

Are Brazilian adolescents eating enough fruits and vegetables? An assessment using data from the Study of Cardiovascular Risk in Adolescents

Abstract: Objective To estimate the usual consumption of fruits and vegetables by Brazilian adolescents. Methods We used 24-hour dietary recall data from the Study of Cardiovascular Risk in Adolescents conducted in 2013-2014 with 71,740 adolescents between 12 and 17 years old. The usual consumption of fruits and vegetables was estimated in the Statistical Analysis Software using the model of the United States National Cancer Institute, and evaluated according to sex, age, place of residence, economic class, and nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In the present study, most respondents reported a higher frequency of F&V consumption than the other types of food categories presented (meat/eggs, carbohydrate, cereals and canned/processed food). Although the design of the questionnaire does not allow quantitative inferences in this regard, household surveys have shown that F&V consumption in Brazil is below the WHO recommendation, of at least 5 servings or 400 g daily (Machado et al, 2016;Brito & Caldas, 2021).This apparent discrepancy with the results of this study may reflect the expression of social desirability, a bias commonly observed in research of this type, where interviewees, consciously or unconsciously, seek to satisfy moral or social expectations when answering a questionnaire, tending to attribute to themselves attitudes that they believe are expected by society, or how they would like to be (Tracey, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, most respondents reported a higher frequency of F&V consumption than the other types of food categories presented (meat/eggs, carbohydrate, cereals and canned/processed food). Although the design of the questionnaire does not allow quantitative inferences in this regard, household surveys have shown that F&V consumption in Brazil is below the WHO recommendation, of at least 5 servings or 400 g daily (Machado et al, 2016;Brito & Caldas, 2021).This apparent discrepancy with the results of this study may reflect the expression of social desirability, a bias commonly observed in research of this type, where interviewees, consciously or unconsciously, seek to satisfy moral or social expectations when answering a questionnaire, tending to attribute to themselves attitudes that they believe are expected by society, or how they would like to be (Tracey, 2016).…”
Section: Discussionmentioning
confidence: 99%